2019
DOI: 10.1002/clen.201800459
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin and Plant‐Growth‐Promoting Rhizobacteria in the Growth and Development of Plants

Abstract: Melatonin is a tryptophan‐based indole molecule found in primitive photosynthetic bacteria to mammals. It performs different functions in plants like rhizogenesis, enhancing plant growth, seed germination, plant yield, biomass production, photosynthesis, circadian rhythm, and fruit ripening. In addition, one of the most significant attributes of melatonin is its antioxidant activity. Moreover, it works as an anti‐stress agent against different biotic and abiotic stresses like drought, salinity, potentially tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 158 publications
(259 reference statements)
0
20
0
Order By: Relevance
“…Hahm et al (2017) also found a significant increase in plant height, fresh weight, dry weight, and chlorophyll contents in abiotic stressed pepper plants inoculated with Brevibacterium iodinum, Rickettsia massiliae, and Microbacterium oleivorans. PGPR stimulates plant growth and development by different processes, such as by increasing nutrient uptake, siderophores production, nitrogen fixation, phosphorus solubilisation, producing phytohormones, and producing secondary metabolites that work as insecticides (Asif et al 2019). Results of current studies show that there is a significant increase in root length, plant height, fresh weight, dry weight, and chlorophyll content in plants applied with melatonin or B. licheniformis without any metal treatment while metals treated plants with melatonin application or B. licheniformis application also enhanced physiological parameters and chlorophyll content significantly as compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hahm et al (2017) also found a significant increase in plant height, fresh weight, dry weight, and chlorophyll contents in abiotic stressed pepper plants inoculated with Brevibacterium iodinum, Rickettsia massiliae, and Microbacterium oleivorans. PGPR stimulates plant growth and development by different processes, such as by increasing nutrient uptake, siderophores production, nitrogen fixation, phosphorus solubilisation, producing phytohormones, and producing secondary metabolites that work as insecticides (Asif et al 2019). Results of current studies show that there is a significant increase in root length, plant height, fresh weight, dry weight, and chlorophyll content in plants applied with melatonin or B. licheniformis without any metal treatment while metals treated plants with melatonin application or B. licheniformis application also enhanced physiological parameters and chlorophyll content significantly as compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…The application of melatonin and PGPR in agriculture enhances plant growth under abiotic and biotic stress without disturbing the natural soil ecosystem. They both are non-toxic substances that increase and stimulate processes involved in plant growth and development (Asif et al 2019).…”
mentioning
confidence: 99%
“…In the past few decades, a series of studies have implicated melatonin as a pivotal molecule in root growth and development (Arnao and Hernández‐Ruiz, 2007, 2015; Pelagio‐Flores et al, 2012; Tan et al, 2012; Zhang et al, 2014b; Arnao and Hernández‐Ruiz, 2015; Wen et al, 2016; Liang et al, 2017; Chen et al, 2019). Furthermore, accumulating evidence suggests that melatonin also acts as a central component in the interaction of roots with microorganisms in the rhizosphere (Jiao et al, 2016; Ma et al, 2017; Asif et al, 2019).…”
Section: Melatonin As a Master Plant (Hormone) Regulatormentioning
confidence: 99%
“…It is biodegradable and safer to be used in organic farming. The excessive intake of melatonin in plants can prevent peroxidation of plant products due to its antioxidant nature and thus increase the shelf life of plants and improve crop yields [111,112]. The main component of plants is chlorophyll, so its preservation and photosynthetic stimulation is of great importance in crop improvement.…”
Section: Role Of Melatonin In Crop Improvementmentioning
confidence: 99%